(untitled) (LEARNing Landscapes, 2011)
Attending to early career teacher attrition as a problem of identity shaping and shifting enabled this narrative inquiry into two beginning teachers’ experiences. We first created a fictionalized survey to show how their experiences could fit neatly into the dominant narratives of early career attrition. We then composed narrative accounts to show each participant’s uniqueness. Seeing beginning teacher attrition through this lens allowed us to become attentive to sustaining moments in these teachers’ lives.